Left-sided appendicitis managed laparoscopically: a case report - Tamara B. AlKeileh; Sali Elsayed; Raheemah Mahomed Adam; Mozamil Nour; Tarun Bhagchandi (Journal of Medical Case Reports, 2024)
Abstract Background Appendicitis is one of the most common causes of acute abdominal pain and remains the most common abdominal-related emergency seen in emergency room that needs urgent surgery (Yang et al. in J Emerg Med 43:980–2, 2012. 10.1016/j.jemermed.2010.11.056, Wickramasinghe et al. in World J Surg 45:1999–2008, 2021. 10.1007/s00268-021-06077-5). The characteristic presentation is a vague epigastric or periumbilical discomfort or pain that migrates to the lower right quadrant in 50% of cases. Other related symptoms, such as nausea, anorexia, vomiting, and change in bowel habits, occur in varying percentages. The diagnosis is usually reached through comprehensive history, physical examination, laboratory tests, and radiological investigations as needed. Nowadays, computed tomography of the abdomen and pelvis is considered the modality of choice for definitive assessment of patients being evaluated for possible appendicitis. Anatomical variations or an ectopic appendix are rarely reported or highlighted in literature. Case presentation Left-sided appendicitis is a rare (Hu et al. in Front Surg 2022. 10.3389/fsurg.2022.896116) and atypical presentation and has rarely been reported. The majority of these cases are associated with congenital midgut malrotation, situs inversus, or an extremely long appendix (Akbulut et al. in World J Gastroenterol 16:5598-5602, 2010. 10.3748/wjg.v16.i44.5598). This case is of significance to raise awareness regarding an anatomical variation of the appendix that might delay or mislead diagnosis of appendicitis and to confirm safety of a laparoscopic approach in dealing with a left-sided appendicitis case (Yang et al. in J Emerg Med 43:980–2, 2012. 10.1016/j.jemermed.2010.11.056). We report a case of left-sided appendicitis in a 12-year-old child managed successfully via a laparoscopic approach. Conclusion Appendicitis remains the most common abdominal-related emergency that needs urgent surgery (Akbulut et al. in World J Gastroenterol 16:5598–5602, 2010. 10.3748/wjg.v16.i44.5598). Left-sided appendicitis is a rare (Hu et al. in Front Surg 2022. 10.3389/fsurg.2022.896116, Hu et al. in Front Surg 9:896116, 2022. 10.3389/fsurg.2022.896116) and atypical presentation and has rarely been reported. Awareness regarding an anatomical variation of the appendix and diagnostic modalities on a computed tomography scan help avoid delay in diagnosis and management of such a rare entity (Vieira et al. in J Coloproctol 39(03):279–287, 2019. 10.1016/j.jcol.2019.04.003). A laparoscopic approach is a safe approach for management of left-sided appendicitis (Yang et al. in J Emerg Med 43:980–2, 2012. 10.1016/j.jemermed.2010.11.056, Hu et al. in Front Surg 9:896116, 2022. 10.3389/fsurg.2022.896116).